Evaluation of Electricity Supply System Selection at an Indonesian Upstream Oil and Gas Company’s Power Plant Using the Ahp-Topsis Method to Improve Operational Performance in Oil Production Lifting - Febrian Surya Perkasa (International Journal Labs, 2026)
The reliability of electricity supply systems is a critical factor in supporting continuous oil production operations in the upstream oil and gas industry, particularly for artificial lift facilities such as Electrical Submersible Pumps (ESP). Interruptions in electricity supply may lead to unplanned shutdowns, production losses, and operational inefficiencies. This study aims to evaluate alternative electricity supply systems for an upstream oil and gas company’s power plant and develop an appropriate decision-making model based on technical, economic, and operational considerations. The study employed a quantitative decision-making approach using the Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. Data were collected from operational reports, electricity supply alternatives, cost estimations, and expert assessments. The AHP method was applied to determine the priority weights of evaluation criteria, while TOPSIS was used to rank the available alternatives. The results indicate that cost was the most influential criterion in the decision-making process, followed by operational reliability, maintenance aspects, and failure impact. The TOPSIS analysis showed that the PLN electricity supply system integrated with Super Ultima service and Dynamic Rotary Uninterruptible Power Supply (DRUPS) achieved the highest preference value compared with other alternatives. This study contributes a structured evaluation model for selecting reliable electricity supply systems in upstream oil and gas operations. The proposed approach can support strategic decision-making to improve production continuity, operational resilience, and energy sustainability.